Enhancing Social Skills in Physically Disabled Students through Inclusive Social Studies Curriculum in Secondary Schools - Sogen, Maria (SOSEARCH : Social Science Educational Research, 2025)
Inclusive education aims to provide equal opportunities for all students, including students with physical disabilities, to develop according to their potential. One important area in education is the subject of Social Studies, which can play a significant role in developing the social skills of students with physical disabilities. This research aims to analyze the implementation of an inclusive Social Studies curriculum in secondary schools, focusing on enhancing the social skills of students with physical disabilities. The method used is a qualitative approach with case studies in several secondary schools that implement inclusive education. The research results show that implementing an inclusive Social Studies curriculum can improve the social skills of students with physical disabilities, although there are challenges related to resource limitations and teachers' understanding. It is hoped that these findings can contribute to the development of a more inclusive curriculum in secondary schools in Indonesia.